Restored topography of the Po Plain‐Northern Adriatic region during the Messinian base‐level drop—Implications for the physiography and compartmentalization of the palaeo‐Mediterranean basin. (10th June 2018) - Amadori, Chiara; Garcia‐Castellanos, Daniel; Toscani, Giovanni; Sternai, Pietro; Fantoni, Roberto; Ghielmi, Manlio; Di Giulio, Andrea
Abstract: The Messinian Salinity Crisis (MSC) involved the progressive isolation of the Mediterranean Sea from the Atlantic between 5.97 and 5.33 Ma, and a sea‐level fall whose timing, modalities, and magnitude remain actively debated. At that time, the central Mediterranean was undergoing strong tectonic activity due to the rollback of the Adria slab and eastward migration of the Apenninic belt. The combined effects of the post‐evaporitic MSC sea‐level drop and morphostructural changes (due to the Intra‐Messinian phase) resulted in a regional unconformity, which shows erosive markers and conformable relationships with the Messinian and Mio–Pliocene boundary in the Po Plain and Northern Adriatic Foreland. Here, we produce a palaeotopographic reconstruction of the Po Plain‐Northern Adriatic region (PPNA) during the Messinian peak desiccation event based on such regional unconformity. We mapped this surface through wells and 2D seismic data form Eni's private dataset. The unconformity shows V‐shaped incisions matching the present‐day southern Alpine valleys and filled with Messinian post‐evaporitic and Pliocene deposits, suggesting that the modern drainage network is at least of late Messinian age. The Messinian unconformity has been restored to its original state through flexural‐backstripping numerical modelling. The resulting landscape suggests a maximum sea‐level drop of 800–900 m during the MSC peak, and is consistent with stratigraphic and sedimentologic data provided by previous works. The modelled shoreline separates the subaerially eroded land from an elongated basin composed by two ca . 400 and 1, 000 m deep depocentres during the maximum sea‐level drop. These results suggest that the Mediterranean was split in at least three sub‐basins subject to independent base levels, fresh‐water budgets, and flexural responses during the maximum lowstand.